Implementation of the RADEC (Read, Answer, Discuss, Explain, Create) model integrated culturally responsive teaching to improve students's 4C skills - Sukmawati, Ina; Imron, Ali; Soesanti, Soesanti (Universitas Negeri Malang, 2024)
This study addresses the low levels of 4C skills (critical thinking, creativity, communication, collaboration) among students, which adversely affects their thinking processes and soft skills, failing to meet 21st-century educational competency standards. Effective interventions are needed to enhance these skills so that students can thrive in a complex global environment. This research evaluates the effectiveness of the RADEC model (read, answer, discuss, explain, create) when integrated with Culturally Responsive Teaching (CRT) to improve 4C skills in students. The RADEC model incorporates activities relevant to students' cultural backgrounds, such as reading materials using tradition content, answering questions, collaborating in discussions, and creating products. The study conducted in class VIII-E of SMP Negeri 3 Surabaya using the Classroom Action Research (CAR) method over two cycles, found a significant increase in 4C skills. The average score rose from 58.86 (fair category) in the first cycle to 78.08 (good category) in the second cycle. Success factors include providing infographic reading materials containing local tradition content that aligns with the student's cultural background, forming class agreements to strengthen learning dynamics, and increasing student involvement in each stage of the RADEC model. Thus, the RADEC model integrated with the CRT approach proved effective in improving 4C students, thereby supporting the achievement of 21st-century educational competencies.